Expression of the relation of precedence in NGN with the subordinate part of time in Russian (on the material of works of art by Russian writers) (The Peerian Journal, 2022)
The article analyzes the ways of linking sentences in NGN with clauses of time, including complex sentences expressing precedence values. In sentences with the meaning of precedence, they report such a temporal relationship between two events when the phenomenon named in the main part precedes the phenomenon named in the subordinate clause. Information is given about the main means of conveying the meaning of precedence with the help of conjunctions, the main semantic components of which are the meanings of simultaneity and diversity (order) of situational coincidences in the main part of a complex sentence in time. about a particular nature, specifying the main temporal feature, an indication of a complete or partial coincidence in time, the absence or presence of an interval and its duration, a limiting moment, regularity, lead, prematureness, unexpectedness of meaning, which can be expressed by the semantics of the union or refined using special concretizers connected to the union. The material for the study was examples from the works of Russian writers.null